Service quality and customer satisfaction towards Kedai 1 Malaysia at Matang, Kuching / Benadrian Rosta Shaelabo Tahim - Tahim, Benadrian Rosta Shaelabo (Faculty of Business and Management, Universiti Teknologi MARA, 2015)
In today's increasingly competitive market, the bottom line of a firm's marketing strategies and tactics is to make profits and contribute to the growth of the company. Therefore, mini market is one of the major movers in agrifood market today. In Kuching, there are several supermarket, such as Alvin Convenience Store, Seven Eleven, KK Store, and Choice Ria. Service quality and level of customer satisfaction are global issues that can affect all organizations, whether it large or small, profit or non-profit, and global or local (Yap and Kew, 2008). Thus, Zain and Rejab (1989) assumed that household income can influence consumers' attraction to the different types of outlets. Similarly, quality of the service and customer satisfaction has long been recognized as playing a crucial role for success and survival in today's competitive market. Moreover, service quality and level of customer satisfaction also as a key important part to make customer re-patronage. Nowadays, the retailers tried to looks for international options because of struggle of the market share and international expansion as the key to continued growth (World Retail Congress, 2008). However, differing consumer needs in international markets defined that international retailers understand local preferences (Etger and Rachman-Moore, 2007).